Sastra dan Sastrawan Jawa Timur di Era Pandemi: Tinjauan Respons Pembaca - Ahmadi, Anas; Darni; Yulianto, Bambang (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to explore East Javanese literature and writers during the pandemic through the perspective of reader response. This study uses an interpretive qualitative approach. The informants in this study were professional literary readers and ordinary literary readers. as many as 84 respondents have responded to the Indonesian Literature Reader form in East Java from various categories with a distribution of 66.3 percent of undergraduate students; 18.8 percent of Lecturers; 8.4 percent of Teachers; 4.2 percent of General; Researchers and Doctoral students got the same result, namely 1.1 percent. Data collection techniques were carried out by means of interviews and questionnaires. The results of the study show the following. First, it represents the psychology of the author.â€ 58.9 percent of respondents answered that the literary work represented the psychology of the author, 28.4 percent did not know and 12.6 percent did not. Second, the literary work represents the author’s psychology, as many as 58.9 percent answered yes. While at least answering the literary work does not represent the psychology of the author, which is 12.6 percent. Third, the psychology understood by the reader, namely Personality Psychology (existential, behavioral, psychoanalytic, humanistic) with 28.4 percent answered yes, while at least 1.1 percent answered Masculinity Psychology and Mass Psychology. Indonesian writers in East Java tend to bring up Javanese human psychology in their literary works?â€ Of these questions, 52.6 percent of respondents answered that Indonesian writers in East Java tended to bring up Javanese human psychology in their literary works, as many as 42.1 percent answered maybe and 5.3 percent answered that Indonesian writers in East Java tended not to bring up Javanese human psychology in their literature. his literary works.